Terahertz Emission of Gallium Arsenide on Textured p-type Silicon (100) Substrates Grown via Molecular Beam Epitaxy - Karl Cedric P. Gonzales; Karim M. Omambac; Elizabeth Ann P. Prieto; Jessica Pauline C. Afalla; Maria Herminia M. Balgos; Rafael B. Jaculbia; Armando S. Somintac; Arnel A. Salvador; Elmer S. Estacio (Journal of Physics and Its Applications, 2018)
This study presents the terahertz (THz) emission of molecular beam epitaxy (MBE)-grown Gallium Arsenide (GaAs) on surface textured p-type Silicon (p- Si) (100) substrates. Surface texturing was achieved by anisotropic wet chemical etching using 5% wt Potassium Hydroxide (KOH): Isopropyl alcohol (IPA) (50:1) solution for 15, 30, 45, and 60 minutes. Reflectivity measurements for the textured p-Si(100) substrates indicated that the overall texturing increases with longer etching times. Raman spectroscopy of the post-growth samples confirmed GaAs growth. The THz emission intensities were the same order of magnitude. The GaAs grown on p-Si(100) textured for 60 minutes exhibited the most intense THz emission attributed to the increased absorption from a larger surface-to-volume ratio due to surface texturing. All GaAs on textured p-Si(100) samples had frequency bandwidth of ~2.5 THz.